A comparison of intersegmental joint dynamics to isokinetic dynamometer measurements - Kaufman, Kenton R.; An, Kai-Nan; Chao, Edmund Y.S. (Journal of biomechanics, 1995)
This study quantified the errors associated with measurements obtained using an isokinetic dynamometer for knee evaluation at 60° and 180° s −1. Five normal subjects were tested. A triaxial electrogoniometer was used to measure the kinematics. A custom-designed load cell was used to measure the three orthogonal components of the reaction force applied by the isokinetic dynamometer to the leg. The inverse dynamics problem was solved to obtain the intersegmental dynamics at the knee joint. These data were compared to those obtained from the isokinetic dynamometer. The results indicate that the knee motion recorded by the isokinetic dynamometer was in error by 7–9° during flexion and 10–13° during extension. The isokinetic dynamometer recorded knee flexions which were less than actual during the flexion portion of the exercise and greater than actual during extension. The duration of constant velocity was limited based on the speed selected. The knee moment was in error by 5 Nm during flexion and 25–29 Nm during extension. The use of a gravity correction factor reduced the knee moment error during extension but increased it during flexion.